The safety and effectiveness of mirabegron in Parkinson's disease patients with overactive bladder: a randomized controlled trial. (2nd January 2022) - Moussa, Mohamad; Chakra, Mohamad Abou; Dabboucy, Baraa; Fares, Youssef; Dellis, Athanasios; Papatsoris, Athanasios
Abstract: Purpose: To assess the safety and effectiveness of mirabegron in patients with PD complaining of overactive bladder (OAB). Patients and methods: From January 2017 to November 2020, we performed a prospective randomized, double-blind, placebo-controlled trial that enrolled PD patients with symptoms of OAB. The total duration of the study was 13 weeks, comprising a 1-week screening period and a 12-week treatment period. A total of 110 patients were randomized in one of two groups: treatment group (mirabegron 50 mg) or placebo group. The primary outcomes of our study were the change from baseline in OAB symptom score (OABSS) and the overactive bladder questionnaire short form (OAB-q SF) score. The secondary outcomes were the change from baseline in the mean number of micturitions/24 hours, the mean number of urgency episodes/24 hours, the mean number of urgency incontinence episodes/24 hours and the mean number of nocturia episodes/night, volume voided/micturition (ml) as recorded on a 3-day bladder diary. Safety assessments included adverse events, electrocardiogram, QT corrected for heart rate using Fridericia's correction (QTcF) interval and blood pressure and pulse rate measurements. Results: There was a significant improvement in the primary outcome and secondary outcome measures in the treatment group compared to the placebo group. Adverse events were mild and the same in the two groups. The cardiovascular safety profile was high. This study is limited by its sample size and its short follow-up period. Conclusions: Mirabegron is a promising drug to control OAB symptoms in patients with PD with an excellent safety profile.